Hybrid Vibration Energy Harvester Based On Piezoelectric and Electromagnetic Transduction Mechanism - Ab Rahman, Mohd Fauzi; Kok, Swee Leong; Mat Ali, Noraini; Rostam Affendi, Hamzah (2013)
Vibration energy harvester converts kinetic energy from ambient vibration into electrical energy. Many energy harvesters in the literature use single element transducer, either piezoelectric, electromagnetic or electrostatic for above purpose. In this paper, a hybrid based energy harvester that integrates with both, piezoelectric and electromagnetic transducers is developed and examined. The energy harvester uses four pole magnets arranged onto a piezoelectric cantilever beam free end, to produce stronger magnetic field over a stationary coil. When the harvester is excited by an external vibration, both piezoelectric and electromagnetic generates electrical energy or power. Experimental results shows that piezoelectric capable to generate optimum power of 2.3mW in a 60k resistive load, while electromagnetic generates 3.5mW power in a 40 resistive load, when vibrated at its resonant frequency 15Hz, and at 1g (1g=9.8ms-2) acceleration. By efficiently integrating both piezoelectric and electromagnetic transducers, more power could be generated as compared to a single transducer over its size.